PATHOPHYSIOLOGY AND MANAGEMENT OF IRON DEFICIENCY IN HEART FAILURE : A LITERATURE REVIEW - Hertanto, Yoseph Jeffry; Kusuma, A.A.Ngr. Anindya (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
When the availability of iron is insufficient to meet the needs of the body with or without anemia, it is classified as iron deficiency characterized by a serum ferritin concentration of less than 100 ng/ml or a 100-299 ng/mL with a transferrin saturation (TSAT) less than 20% in patients with heart failure. Reduced intake, low iron absorption due to increased hepcidin secretion, iron secretion in the reticuloendothelial system as a result of inflammation, and blood loss from the gastrointestinal system are mechanisms believed to cause iron deficiency (ID). With 25–42% of Heart Failure (HF) patients having ID when anaemia is absent, ID is frequent regardless of the presence of anaemia in HF. ID management in HF requires a shift in the therapeutic focus from dealing with anemia to iron supplementation, both oral and intravenous (IV). Current guidelines also support the use of IV iron. New drugs also focus on iron metabolism, which these drugs are still in development.